(untitled) (Architecture Image Studies, 2025)
This study investigates the development of modern logistics systems in Central Asia, focusing on Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, and Turkmenistan. It aims to identify the current challenges and key factors affecting logistics efficiency and to propose strategic guidelines that promote modernization, integration, and sustainability in the region’s logistics sector. A mixed-methods approach was employed, integrating quantitative analysis of secondary data with qualitative interviews from logistics experts. The results revealed steady improvement in logistics performance across Central Asia over the past decade, with Kazakhstan leading in LPI scores and digital readiness. A strong positive correlation was found between infrastructure quality and customs efficiency, confirming the importance of physical infrastructure in trade facilitation. The study concludes that achieving logistics modernization in Central Asia requires an integrated strategy combining infrastructure coordination, technological innovation, and policy harmonization. Recommendations include establishing a Regional Logistics Coordination Council (RLCC), promoting public–private partnerships, accelerating e-customs systems, investing in human capital, and integrating green logistics practices. These measures can transform Central Asia into a competitive, efficient, and sustainable logistics hub connecting Asia and Europe.